The origins of terrorism cross-country estimates on socio-economic determinants of terrorism - Andreas Freytag; Jens J. Krüger; Daniel Meierrieks; Friedrich G. Schneider (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
To expand our knowledge about an appropriate anti-terror strategy, it is indispensable to assess the underlying causes of terror. We examine social and economic conditions in the country of origin of terrorist attacks, claiming that low opportunity costs of terror, e.g. approximated as slow growth and poor institutions raise the propensity of terror and the willingness in the population to support terror. Using a mixed effects Poisson regression model, we are able to show that unfortunate socio-economic conditions in a country are suitable to reduce the opportunity cost for potential terrorists and increase the likelihood of terrorist attacks originating from a specific country. Interestingly, this effect is relevant after a certain level of development has been reached. We therefore distinguish between the OECD, Europe and Islamic countries.
Keywords: P16; F15; C25; 330; Terror attacks; openness; discrete choice analysis; institutions; Politische Gewalt; Politische Stabilität; Soziale Stabilität; Opportunitätskosten; Diskrete Entscheidung; OECD-Staaten; Europa; Islamische Staaten